A methodology for scheduling the economic purchase of energy in a competitive electricity market - Sioson, Vicente C. (2001)
The Philippine electric power industry will soon be restructured and become competitive. In this environment, it is imperative that distribution companies purchase energy in the most economic manner to protect profitability and market share. This study developed a methodology for scheduling the economic purchase of energy. The proposed methodology minimizes the annual energy purchase cost by optimally allocating energy purchases from two types of energy market instruments - bilateral contract and the spot market. It involved the modeling of the load, bilateral contract and spot market characteristics as decision variables in linear programming optimization. The methodology is applied in an actual distribution system operating in a hypothetical competitive electricity market environment. The computed results generate the optimal schedule of energy purchases from both market instruments. Case studies show that the optimal schedule is sensitive both to the prices of both energy market instruments.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric utilities -- Costs. -- Philippines; Electric utilities -- Management -- Linear programming. -- Philippines